A inferencia na compreensao do texto escrito : oficinas de oralidade, leitura e escrita para educandos do ensino fundamental em Picos no Estado do Piaui - Sampaio, Ana Karina Barbosa (2005)
This Master essay deals with inductive understanding for local produced texts written by students in Basic Education Local Network, Picos, State of Piaui, Brazil. We deem local produced texts as those texts written by individuals involved in the research social-cognitive environment. Our purpose, from a comprehensive point of view, is to discuss the inductive process for local circulating text readers as a starting point for their social-cultural universe increasing. Therefore, in order to establish which induction types were performed by 8th grade students who read a sole text, we analyzed such induction types. In this essay, we deem reading as the knowledge building process which occurs through an interaction between text and reader. Reader gives meaning to his/her readings, i.e., he/she understands the written text using inferences, which inferences were defined by Marcuschi (1985) as being a reader cognitive capability for building new propositions from other given propositions. Inferences are methods performed by the reader in the reading interaction process. Inferences are basic for understanding, since reader fulfills at the interaction time holes left in text, when there occurs prior acknowledge activation which acknowledge is stored in memory, and it is organized into a structure forming a cognitive model. We performed the research in two schools: Frei Damião (inside city zone), and Acelino Araújo (rural zone). Data were collected from a social-cultural questionnaire, and from the performance of two reading workshops, writing and voicing, in which the understanding of poems Rios Guaribas and Rios sem Discurso was suggested. The major part of students performed analogical-semantic type inferences, and they exhibited a greater understanding interaction in connection with Rio Guaribas poem, a local produced text. Such event is explained for this text dealing with questions that are closer to students social-cognitive environment, while otherwise in relation to Rios sem Discurso poem understanding it was more difficult, which is explained by a fault in linguistic acknowledgement activation in relation to certain lexical items.